Answer
The quadratic expression \(2a^{2} - 24a + 20\) can be factored as \(2(a - (6 + \sqrt{26}))(a - (6 - \sqrt{26}))\).
Solution
Certainly! Let's analyze and work with the quadratic expression you've provided:
\[
2a^{2} - 24a + 20
\]
### Step 1: Factor Out the Greatest Common Factor (GCF)
First, identify and factor out the greatest common factor from all the terms in the expression.
- **GCF of 2, -24, and 20 is 2.**
\[
2a^{2} - 24a + 20 = 2(a^{2} - 12a + 10)
\]
### Step 2: Attempt to Factor the Quadratic Expression
Now, focus on the quadratic part inside the parentheses:
\[
a^{2} - 12a + 10
\]
To factor this, we look for two numbers that:
1. **Multiply to give the constant term (+10).**
2. **Add up to give the coefficient of the middle term (-12).**
Let's list the pairs of factors for 10:
- \(1 \times 10\)
- \(2 \times 5\)
Considering the sign (since the constant term is positive and the middle term is negative), both numbers should be negative:
- \(-2 \times -5 = 10\) (But \(-2 + (-5) = -7 \neq -12\))
- \(-1 \times -10 = 10\) (And \(-1 + (-10) = -11 \neq -12\))
**None of these pairs add up to -12**, which means the quadratic doesn't factor neatly with integer coefficients.
### Step 3: Solve for the Roots Using the Quadratic Formula
Since the quadratic doesn't factor easily, we'll use the quadratic formula to find its roots:
\[
a = \frac{-b \pm \sqrt{b^{2} - 4ac}}{2a}
\]
For the quadratic \(a^{2} - 12a + 10\):
- \(a = 1\)
- \(b = -12\)
- \(c = 10\)
Plugging these into the formula:
\[
a = \frac{12 \pm \sqrt{(-12)^{2} - 4 \cdot 1 \cdot 10}}{2 \cdot 1} = \frac{12 \pm \sqrt{144 - 40}}{2} = \frac{12 \pm \sqrt{104}}{2} = \frac{12 \pm 2\sqrt{26}}{2} = 6 \pm \sqrt{26}
\]
### Step 4: Express the Factored Form with Real Roots
Using the roots found, the factored form of the quadratic expression is:
\[
2a^{2} - 24a + 20 = 2(a - (6 + \sqrt{26}))(a - (6 - \sqrt{26}))
\]
### Summary
- **Factored Form:** \(2(a - (6 + \sqrt{26}))(a - (6 - \sqrt{26}))\)
- **Vertex Form (Completing the Square):**
Alternatively, you can express the quadratic in vertex form by completing the square:
\[
2a^{2} - 24a + 20 = 2\left[(a^{2} - 12a) + 10\right] = 2\left[(a - 6)^{2} - 26\right] = 2(a - 6)^2 - 52
\]
This form is useful for easily identifying the vertex of the parabola represented by the quadratic equation.
If you have a specific operation you'd like to perform on this expression (e.g., graphing, finding the vertex, optimizing, etc.), please let me know!
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution